Sensitivities of biomechanical assessment methods for fracture healing of long bones. Issue 7 (July 2015) - Chen, G.; Wu, F.Y.; Zhang, J.Q.; Zhong, G.Q.; Liu, F.
Highlights Provides a theoretical framework that relates the whole-bone stiffness to the healing degree at the fracture site; Explains why the whole-bone stiffness is insensitive to the healing process of fractured long bones in the late stage of healing; Provides theoretical explanations to the interesting experimental results observed by Henry and others; Verify the conclusions obtained from the simplified model by the finite element simulations of the artificial femur.